IMPLEMENTATION OF SUSTAINABLE PROFESSIONAL DEVELOPMENT FOR HIGH SCHOOL TEACHERS - Marhawati, Besse; Rahman, Nurdayanti A. (International Research-Based Education Journal, 2022)
This study aims to describe (1) the implementation of teacher self-development (2) the teacher's scientific publications, and (3) the implementation of the teacher's innovative work. The method in this study uses a quantitative approach to the type of percentage. The subjects of this study were 60 high school teachers for Tidore's disability. The sampling technique in this study used a random sampling technique. Data collection techniques using questionnaires, observation, and documentation and data analysis using descriptive analysis of presentations. The results show that: (1) the implementation of teacher self-development is in very good criteria, (2) the teacher's scientific publications are in good criteria, and (3) the implementation of the teacher's innovative work is very good. This shows that teachers in high schools in the Tidore sub-district have the will and active participation in teacher continuous professional development activities which are shown with very good results. For this reason, it is suggested to: (1) principals to always provide opportunities and motivation for teachers to develop their professionalism, and (2) teachers are expected to continuously develop self-quality related to their professionalism.